1978
DOI: 10.1179/msc.1978.12.2.64
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic oxidation and crack growth during high strain fatigue of low alloy steel

Abstract: This paper attempts to assess the contribution of oxidation to crack growth during high strain fatigue of a Cr-Mo-V steel at 550°C from three separate oxidation studies. Stress-free data are clearly inapplicable to the highly strained crack tip and so it is first shown that internal stresses, as in bainitic material, promote enhanced oxidation. Weight gain experiments on oxide-free fracture surfaces are next described. It is shown that the stored energy of fatigue fracture likewise causes an increase in oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…7 and e.g. [28][29][30][31][32][33][34]. These tests and observations clearly show that the grain boundaries have been affected by some sort of damage mechanism which is not active during rapid cyclic loadings.…”
Section: Dwell Time Damagementioning
confidence: 60%
“…7 and e.g. [28][29][30][31][32][33][34]. These tests and observations clearly show that the grain boundaries have been affected by some sort of damage mechanism which is not active during rapid cyclic loadings.…”
Section: Dwell Time Damagementioning
confidence: 60%
“…vacuum vs. oxygen, and it has been shown that a significant reduction in crack propagation rate is found in vacuum, see e.g. [24][25][26][27][28][29]. These tests and observations clearly show that the grain boundaries have been affected by some sort of mechanism which is not active in rapid cycling.…”
Section: Hold Time Effectsmentioning
confidence: 69%
“…48 Typical values of d c lie in the range 1-2610 23 and from the 24 h dwell time crack growth results of 316L steel at 600uC 13 a good fit to the data is obtained by assuming d c 53610 23 in equation (23a). The net effect is to raise the value of Q above that for continuous cycling, and by implication the effective value of B, the crack growth rate at unit depth.…”
Section: Damage Factors In Creep-fatiguementioning
confidence: 99%